Faktor-Faktor yang Mempengaruhi Return On Assets - Zulfa Khusnul Armyta; Suhendro; Yuli Chomsatu Samrotun (JRB-Jurnal Riset Bisnis, 2020)
The main purpose of the establishment of a company is to obtain profit. In an effort to achieve these objectives, it is necessary to have a good management of financial performance so that it can achieve optimal profits. A company can be said to be able to manage financial performance well if the company is able to maintain economic conditions in any situation from its ability to meet financial obligations, is able to use its assets to make a profit, and can develop its business. In this study to measure the level of development of companies in the consumer goods industry sector using profitability ratios. One measure of profitability ratios is ROA (Return on Assets) in a company. This study aims to examine the Current Ratio, Total Asset Turn Over, Company Size and Sales Growth on Return on Assets in the consumer goods industry sector in the period 2013-2018. Sampling using purposive sampling and obtained 144 observation samples from 24 companies. Hypothesis testing is done using multiple linear regression. The results of hypothesis testing show that the Current Ratio and Firm Size variables have a significant effect on Return On Assets, while the Total Asset Turn Over and Sales Growth variables have no effect on Return On Assets.